An extravagant death - Finch, Charles (Charles B.) (New York : Minotaur Books, 2021)
London, 1878. With faith in Scotland Yard shattered after a damning corruption investigation, Charles Lenox's detective agency is rapidly expanding. But when Prime Minister Benjamin Disraeli offers him the opportunity to undertake a diplomatic mission for the Queen, Lenox welcomes the chance to satisfy an unfulfilled yearning: to travel to America.
Keywords: Lenox, Charles (Fictitious character) -- Fiction; Private investigators -- England -- London -- Fiction; British -- United States -- Fiction; New York (N.Y.) -- History -- 19th century -- Fiction; Newport (R.I.) -- History -- 19th century -- Fiction; Detective and mystery fiction; Historical fiction